miRNA Expression Characterizes Histological Subtypes and Metastasis in Penile Squamous Cell Carcinoma - Ayoubian, Hiresh (Cancers (Basel), 2021)
SIMPLE SUMMARY: Penile squamous cell carcinoma (PSCC) is the most common type of penile cancer (PeCa) and is associated with human papillomavirus (HPV) in about 50% of cases. It is of high clinical impact to identify patients who are at high risk of metastasis and are likely to benefit from adjuvant therapies. Today, valid prognostic biomarkers are scarce in penile cancer. In the present study, we attempted to identify miRNAs involved in tumor development and metastasis in distinct histological subtypes with or without HPV infection in PSCC patients. We confirmed that specific miRNAs could serve as potential diagnostic and prognostic markers in single PSCC subtypes and are associated with HPV infection. ABSTRACT: Although microRNAs are described as promising biomarkers in many tumor types, little is known about their role in PSCC. Thus, we attempted to identify miRNAs involved in tumor development and metastasis in distinct histological subtypes considering the impact of HPV infection. In a first step, microarray analyses were performed on RNA from formalin-fixed, paraffin-embedded tumor (22), and normal (8) tissue samples. Microarray data were validated for selected miRNAs by qRT-PCR on an enlarged cohort, including 27 tumor and 18 normal tissues. We found 876 significantly differentially expressed miRNAs (p ≤ 0.01) between HPV-positive and HPV-negative tumor samples by microarray analysis. Although no significant differences were detected between normal and tumor tissue in the whole cohort, specific expression patterns occurred in distinct histological subtypes, such as HPV-negative usual PSCC (95 differentially expressed miRNAs, p ≤ 0.05) and HPV-positive basaloid/warty subtypes (247 differentially expressed miRNAs, p ≤ 0.05). Selected miRNAs were confirmed by qRT-PCR. Furthermore, microarray data revealed 118 miRNAs (p ≤ 0.01) that were significantly differentially expressed in metastatic versus non-metastatic usual PSCC. The lower expression levels for miR-137 and miR-328-3p in metastatic usual PSCC were validated by qRT-PCR. The results of this study confirmed that specific miRNAs could serve as potential diagnostic and prognostic markers in single PSCC subtypes and are associated with HPV-dependent pathways.